Morphometry of and genetic variation in mtDNA of the edible nest swiftlet (Aerodramus fuciphagus thunberg) in Malaysia - Kolade, Oluwaseyi Modupe (2014)
A. fuciphagus (edible nest swiftlets) naturally inhabit the limestone caves of South East Asia, but recently swiftlet ranching in man-made houses has become popular. These swiftlets are of commercial importance because of their unique nests produced wholly of the mucilaginous secretion from the salivary glands and highly valued for their nutritional, aphrodisiac and medicinal properties. Limited works are available on the genetics of this swiftlet, especially in Malaysia. There is also a lack of knowledge about the spatial delineation of the swiftlet species in Malaysia. This study was carried out to elucidate information on genetic variability of A.fuciphagus by analysing seven mtDNA genes (cytb, ND2, ND3, ND5, 12S rRNA, 16S rRNA and COI), with the hope of identifying DNA barcodes for the purpose of traceability of the edible bird nests (EBNs). Morphometric parameters of the birds were also evaluated so that the variations observed among locations may be associated with variations among the molecular markers. For the morphometric study, 33 birds captured humanely from five locations in West Malaysia (Bachok, Kota Bharu and Tanah Merah in Kelantan, Kuala Terengganu in Terengganu, and Sungkai in Perak) were measured for beak thickness, length of beak, tail length, leg length and wing length. There were no significant differences in the beak thickness of the EBN swiftlets from the five locations, while significant (P<0.05) differences were observed for the other parameters among some locations. There were no significant correlation between body weight and beak thickness, beak length, leg length, wing length and tail length there were no association existing between the body weight and morphometric parameters. Generally, there seemed to be no clear pattern of geographical variations for the morphometric traits investigated among the locations. For the mtDNA analysis, DNA samples, extracted from blood, tissue or nests, of 28 EBN swiftlets from six locations (Sungkai in Perak, Tanah Merah in Kelantan, Kuala Terengganu in Terengganu, Kota Tinggi in Johor, Gua Madai and Pitas in Sabah) were used. The DNA was subjected to PCR amplification of seven mtDNA gene loci, namely cytb, ND2, ND3, ND5, 12S rRNA, 16S rRNA and COI. Sequencing of the amplicon revealed a total of 33 haplotypes across the loci. The cytb and ND2 loci had the highest variation with each exhibiting eight haplotypes. The 12S rRNA, 16S rRNA, COI and ND5 loci had five, six, four and five haplotypes, respectively; ND3 had only one. The Tajima’s D showed a negative value for all the loci (P> 0.05), while the Fu and Li’s D values were negatives for all the loci except 16S rRNA. Estimates of genetic differentiation for the mtDNA loci did not show any genetic structure within or between the locations. The median joining network (MJN) tree for all the gene loci showed that the EBN swiftlet populations could not be distinguished geographically. The shared haplotypes suggest high gene flow between locations. The mismatch distributions for all loci were multimodal in shape except for the ND5 locus. The mtDNA loci indicated lack of spatial delineation and the unsuitability of these markers for DNA barcoding. However, the results showed that the overall genetic diversity in the species was relatively high indicating a genetically healthy population. The data obtained from this study will be useful to monitor the effects of swiftlet ranching on the A. fuciphagus population and in the management of the genetics of this species.